2022
DOI: 10.22336/rjo.2022.3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between allergic rhinitis and allergic conjunctivitis (allergic rhinoconjunctivitis) - review

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This is presumably due to the shared properties of the conjunctiva and nasal mucosa — they have the same type of epithelial cells, they show similar allergen reactivity, and both play a role in Immunoglobulin E (IgE)-mediated allergic inflammation, indicating shared pathological mechanisms. Plus, the presence of an anatomical link between the eyes and nasal mucosa through the nasolacrimal duct enables allergic reactions to spread from the conjunctiva to the nose ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is presumably due to the shared properties of the conjunctiva and nasal mucosa — they have the same type of epithelial cells, they show similar allergen reactivity, and both play a role in Immunoglobulin E (IgE)-mediated allergic inflammation, indicating shared pathological mechanisms. Plus, the presence of an anatomical link between the eyes and nasal mucosa through the nasolacrimal duct enables allergic reactions to spread from the conjunctiva to the nose ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Few incidences of benign conjunctivitis typically occur in the majority of patients with ocular allergies. The patient's examinations must include a thorough ocular inspection, biomicroscopy, a Slit-lamp biomicroscopic examination, and additional supplemental diagnostic procedures like an aeroallergen skin probe test [13][14][15] . Even though there are several different types of ocular allergies, perennial and seasonal AC is the mildest and the most prevalent one.…”
Section: Seasonal and Perennial Allergic Conjunctivitismentioning
confidence: 99%
“…Studies have previously demonstrated that the occurrence of AR in adults in China has risen significantly, with the prevalence increasing from 11.1% to 17.6% ( 7 ). AR is often accompanied by other health conditions like asthma and allergic conjunctivitis ( 8 , 9 ). Indeed, research has indicated that clinical asthma is present in 20% to 50% of individuals with AR, while over 80% of patients diagnosed with allergic asthma also experience symptoms of rhinitis simultaneously ( 10 ).…”
Section: Introductionmentioning
confidence: 99%